Match performance variables that differentiated between qualified and eliminated teams in the group stages of the 2018 FIFA World Cup - Kubayi, A.; Larkin, P. (German Journal of Exercise and Sport Research, 2022)
The aim of this study was to analyse how performance variables differed between teams that were eliminated and teams that qualified from the group stage at the 2018 FIFA World Cup. A total of 48 games played by 32 teams during the tournament were analysed using the InStat video analysis system. Mean (M), standard deviation (SD), effect size (ES) and independent t-test were used to analyse the data. The results indicated that qualified teams performed significantly (p< 0.05) better than eliminated teams on performance indicators such as shots on target (ES= 0.83), total passes (ES= 0.89), accurate passes (ES= 0.84), medium passes (ES= 0.80) and ball possession (%; ES= 0.89). A significant difference was observed between qualified and eliminated teams on set-piece goals (p= 0.03; ES= 0.83). The findings indicated that teams eliminated at the group stage had more long passes and counter-attacks compared to teams that qualified for the knockout stages. These results may assist coaches in developing team tactics and training activities to maximise the chances of reaching the knockout stages of the FIFA World Cup.